The implications of culture shock for health educators: Reflections with Barer-Stein - M. L. Arthur (AOSIS, 1996)
Culture shock is an intensely personal universal human experience that may emerge in any cross cultural social encounter. Therefore, it may be deduced that culture shock is an experience that may occur in all spheres of life in which individuals are confronted by world views and life styles that differ from their own whether in terms of health, education or occupation amongst others. It is a situation that calls for adaptation or adjustment on the part of the individual. TTtis article explores the relationship between culture shock and culture adaptation as an aspect of learning which has been developed by Thelma Barer-Stein. Stress is laid on the role of the individual, as health educator, and the choices must make if he/she is to gain an understanding of the community in which he/she serves and to attribute new meanings to the situation by which he/she is confronted